(3GdGbJUGO Gdcdj(B1 (3OQhS h JeGQjf (B: s (3ehLgI dWdHI GddjSGfS aj ejOGf GdYdhe GdGbJUGOjI h GdJLGQjI h Ydhe GdJSjjQ (B/ s - (3YeQhT, HgjIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3eONd ddJMdjd GdGbJUGOj Gdcdj (B((3eaGgje hYehejGJ(B)(3, bjGS eSJhi GdfTGW GdGbJUGOj Gdcdj (B((3eONd dMSGHGJ GdONd GdhWfj(B) (3, GdJhGRf GdGbJUGOj Gdcdj hab GdfehPL GdcdGSjcj, GdJhGRf GdGbJUGOj Gdcdj hab GdfehPL GdcjfRj(B.s
(3GdeQGLYs
Keywords: (3GdGbJUGO Gdcdjs